Sexually transmitted penile amoebiasis in Iran: a case series. Issue 8 (28th August 2012) - Abdolrasouli, Alireza; de Vries, Henry J C; Hemmati, Yahya; Roushan, Azita; Hart, Jason; Waugh, Michael Anthony
Abstract : Objectives: Four cases of penile amoebiasis (PA) presenting as genital ulceration seen among men who practiced unprotected insertive anal intercourse in Tehran are described. Methods: PA was confirmed by observation of motile trophozoites of Entamoeba histolytica from lesions examined by wet mount microscopy. Results: Ulcers were solitary, painful, irregular, discharging and increasing in size. Three heterosexuals and one bisexual had practised insertive anal intercourse in the 2 weeks before diagnosis. Bilateral inguinal lymphadenitis occurred in one case. Direct examination of lesions was positive for the presence of amoebic trophozoites. Complete resolution occurred after treatment with oral metronidazole 800 mg three times daily for 7–10 days. Conclusions: Clinicians need to be aware of cutaneous amoebiasis in sexually active men who practice unprotected insertive anal sex where intestinal amoebiasis is endemic. Wet mount microscopy is a rapid and useful diagnostic test.